A primary intracranial ependymal cyst - Sarkar, S; Pervin, S; Mazumder, U; Riaz, BK; Dey, SK (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):427-9 The abstract of this article is available on the PubMed website